"The Theory of Arabic Grammar in Language Instruction (From the Logic of Language Grammar to the Logic of Thought Grammar)" - merzouk, fatih (El Omda in Linguistics and Discourse Analysis, 2018)
The grammatical theory is one of the linguistic theories that contain the scientific bases to prove it in the language in general and in Arabic in particular; the fact that the theory in the linguistic custom must be included in the foundation of the hexadecimal origin of the syllabus, the foundation, the apostates, the time and the place, These scientific standards have an extension in the Arabic language lesson, especially in the grammar lesson, as the researchers were able to avoid the grammar lesson through these criteria; there was a precise scientific proof of the theory of Arabic grammar; He ordered the logic of pure Arabic grammar. Proceeding from the Arabic grammar is reasonable. It is clear that the theories are branched out by branching out their scientific features, especially when it comes to grammatical theory. This theory, whose scientists were able to lay down their rules in terms of the definition of the method used; they were able to take a way to punctuate the judgments with all rigor. It was then that the text was given to the sculptors who came from afar. In fact, these features made the grammatical theory based on the most powerful. The theory came coherent in its origins. It was solid in its provisions through comprehension. It included all the following studies, The grammarians were able to control the rule from the point of view of mental reasoning and logical judgments; they took out what is contained in the Arab mind to translate it into rules; because grammar rules of evidence